Child Trafficking & Human Trafficking : Legal Aspects and Role of a Doctor - Shagun Thakur; Vikas Gurbani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Counter-trafficking measures are to be implemented at various levels and by various organisations. Themedical professionals also play an important role in this area as in many cases, the victims are first identifiedwhen they require some form of medical attention.A child victim of trafficking is any person younger than 18 years against whom the act of trafficking hasbeen committed.The definition of child trafficking differs from that of trafficking in humans in the respectthat children are considered being vulnerable not only because of their level of maturity and age but alsoother factors.This article highlights the various legal aspects of child and human trafficking in India. The victim oftrafficking may not himself disclose what he is going through, so there are certain points on history andexamination which should arise the suspicion in the mind of the health professional. These signs andsymptoms are mentioned in this article which are collected from various resources. Emergency medicinedepartment has an important role in screening of these victims, although all the departments contribute inidentifying the victims.The article also mentions where India stands compared to its global counterparts in anti-trafficking measures.